Disseminated Neospora caninum Encephalomyelitis and Myositis in a 3-Month-Old Cane Corso Puppy - Abigail L. English; Joshuah B. Klutzke; Stephanie A. Thomovsky; Nobuko Wakamatsu (Veterinary Sciences)
We present a case of fatal disseminated neosporosis in a 3-month-old Cane Corso puppy. The puppy presented to the Purdue Veterinary Hospital emergency service with a 1-week history of progressive left hindlimb lameness. On presentation, the puppy was nonambulatory paraparetic. Signs progressed over two days to nonambulatory tetraparesis, and decreased to absent limb reflexes, cranial nerve deficits, and dull mentation. Blood work showed eosinophilia, elevated ALT, and extremely elevated creatine kinase at 36,000 IU/L (reference interval 22–491 IU/L). Two days after diagnostics were performed, the puppy experienced acute cardiac arrest, and the body was submitted for necropsy. At necropsy, skeletal muscle in all four limbs was diffusely pale tan. Tan streaks were disseminated through the diaphragm, abdominal wall, and myocardium. Histologically, Skeletal myocytes and cardiomyocytes were frequently degenerative, with abundant lymphohistiocytic inflammation and fibrosis. White matter within the brain and spinal cord was inflamed and contained frequent dilated myelin sheaths and spheroids. A few protozoal cysts were within the brain and skeletal myocytes. Antemortem antibody titers were positive for IgG against Neospora caninum (dilution titer of 1:4096, baseline 1:32), confirming protozoal cysts as Neospora caninum. Disseminated neosporosis is an uncommon but important clinical differential for ascending paresis in young dogs.